A Climate of Justice: An Ethical Foundation for Environmentalism - Brown, Marvin T. (Library of Public Policy and Public Administration, 2022)
This open access book helps readers combine history, politics, and ethics to address the most pressing problem facing the world today: environmental survival. In A Climate of Justice, Marvin Brown connects the environmental crisis to basic questions of economic, social, and racial justice. Brown shows how our current social climate maintains systemic injustices, and he uncovers resources for change through a civic ethics of repair and reciprocity. A must-read for researchers and educators in the area of environmental ethics and those teaching courses in the fields of public policy and environmental sustainability. With the support of more than 30 libraries, the LYRASIS United Nations Sustainable Development Goals Fund has enabled this publication related to SDG13 (Climate Action) to be available fully open access.